Kendala Teknis dan Hukum dalam Proses Penyidikan Tindak Pidana Siber di Indonesia - Muhammad Singgih Imam Wibowo; Akhmad Munawar; Hidayatullah (Jurnal Hukum Lex Generalis, 2024)
This research aims to analyze the technical and legal obstacles faced in the process of investigating cybercrimes in Indonesia. Along with the rapid development of information technology, cybercrime has become one of the biggest challenges in the criminal justice system in Indonesia. This research identified various technical barriers, such as limitations of digital forensic tools and difficulties in collecting distributed evidence across multiple platforms. In addition, legal aspects, including inconsistencies between national regulations and international standards, as well as challenges in cross-jurisdictional cooperation, also influence the effectiveness of investigations. Based on the results of the analysis, this research suggests several strategic steps, including updating regulations, increasing human resource capacity, and strengthening coordination between law enforcement agencies at both the national and international levels. It is hoped that this research can contribute to improving the cybercrime investigation system in Indonesia and support efforts to eradicate cybercrime more effectively.